The Role Of Visionary Leadership In Reducing The Financial Failure Of Banks: An Exploratory Study In A Sample Of Iraqi Commercial Banks - et. al., Waleed Abbas Jebur AL-Daamee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to diagnose the causal relationships between visionary leadership and banking failure through the researcher's reliance on the descriptive-analytical approach by employing the implications of deductive analysis in the fields of theory and practical tests of the model and hypotheses the study. The researcher also adopted the exploratory study methodology in the procedural measurement of the study variables. The study data was collected for a sample of eleven commercial banks in Basra Governorate. It is one of the important banks in the country's economy, facing severe challenges due to the rapid changes in the security, political and economic conditions that have swept the country. The procedures for distributing the questionnaire to officials at the levels of implementing the strategic decisions of the researched banks were, and the number of respondents was (205). The survey tool was designed according to the (Likert) five-point scale, and the data was processed through advanced statistical methods (Smart Pulls) and (Spss v.21) program. The analysis results show that visionary leadership has a strong positive relationship in banks' avoidance of banking failure. This study contributed to uncovering the role of an essential type of leadership, namely visionary leadership. This study also clarified cases of banking failure and the techniques needed to avoid them.